Risk assessment method for soil secondary salinization based on hydrological frequency analysis - Hengli Wang; Zongzhi Wang; Ying Bai; Wenhua Wan; Wensheng Wang; Kun Wang (Ecological Indicators)
Soil salinization represents a major contributor to land degradation globally. Quantitative risk assessment of soil salinization provides the fundamental basis for effective salinity management strategies. However, existing salinization risk assessment methods based on the comprehensive index method exhibit the difficulties of high subjectivity and insufficient quantitative evaluation. In this study, a quantitative assessment methodology for the soil secondary salinization risk was developed on the basis of the frequency distribution of the groundwater depth, employing probabilistic theory and mathematical statistics. The correlation between the groundwater depth and the severity of soil secondary salinization was analyzed. The results demonstrate that groundwater depth serves as the primary risk factor for soil salinization. Furthermore, the statistical characteristics of groundwater depth effectively indicate secondary soil salinization risk. Based on uncertainty theory, we propose a novel definition of soil salinization risk and derive a corresponding theoretical equation for calculating secondary soil salinization risk. Finally, we establish a comprehensive risk assessment model. A risk evaluation framework and steps were proposed and applied in Xinxiang city, which is greatly affected by salinization in China, to verify the practicability and accuracy of the established method. This study contributes to the theory and methods of secondary salinization risk assessment and could represent a new direction of research.